V2G from Electric School Buses: The Impact on Children, Communities and Supply Chain Management - Prakash, Pallav (International Journal of Supply Chain Management, 2023)
Electric vehicles (EVs) are rapidly acquiring significance in the day-to-day lives of the masses and so is the vehicle to grid technology (V2G). While nations across the globe are pushing for rapid adoption, they have to first address the challenges of grid overload and shutdown and intermittency of electricity supply from renewable sources. V2G technology provides a respite but is not without drawbacks. The electric school buses (ESBs), that remain idle for most part of the day, have emerged as the preferred choice in implementing V2G with obvious health, environmental and economic advantages. ESBs may appear initially as the new solution to public transportation, but it will affect our lives in many aspects besides being the environmental solution to public transportation. These EVs can be used for multifaceted functionalities than just being restricted to be a charging tool, a load balancer for the Grid or just as a means of transportation. In our digitized world the need for uninterrupted energy has attained a lot of importance. Innumerable solutions and diversified usage of EVs can be innovated from EVs existing energy sources (the batteries) to its in-built technological systems. The V2G concept, combined with smart grid technologies, offers an optimal system for the realization of the benefits offered to users, utilities, economics and the environment by electric vehicles. Electric school buses (ESB) can be used effectively to build a cleaner supply chain. This article delves into the benefits that ESBs confer upon school children, upon the communities and the economy. The health, environmental and economic benefits outweigh the initial costs involved with acquisition and usage of ESB fleet. The sustainability of using the V2G technology using school buses in supply chain management, especially where the supply chain is spread across remains a concern and warrants further research. Nevertheless, beyond a doubt, electric school buses will play a significant role so far as improving the health of the children and communities and reducing emission of pollutants is concerned.